The Implementation of Diversion by the Investigator of Bandung Police Department Towards Narcotics Cases Conducted by Children - Herdiansyah Akhmadi; Ijud Tajudin (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
Narcotics crime is not only done by someone who has entered adulthood. In fact, the involvement of children in the vicious circle of narcotic crime has often been encountered. In response, the Government issued Law No. 11 Year 2012 on the Criminal Justice System for Children to accommodate children with legal problems. In the Criminal Justice System Law for Children found a concept that is not encountered in another law that is diversion. Diversion is the transfer of the settlement of child cases from criminal justice process to process outside of criminal justice process. The requirement for a child to be made a diversion effort is a criminal threat against the child is not more than 7 (seven) years and not the repetition of criminal offense. Drug Division of Bandung City Police Department in the period of investigation 2015 - 2017 has handled 7 (seven) narcotics cases done by the child. The success rate of diversion in the BCPD is more than 50%, although not a few factors can hamper the enforcement of diversion itself. This study aims to find out how the process of diversion conducted by BCPD Drug Division and whatever obstacles they face. This research was conducted using normative juridical approach method and empirical juridical research specification, that is by examining secondary data consisting of primary law material, secondary law material, and field research in the form of a third party related interview. It can be argued that the application of diversion is not easy but does not make the process of applying diversion of children stalled. In addition to the necessary reforms in the aspect of a legislative establishment, it is also necessary to develop the infrastructure and capacity building of the law enforcement in the implementation of the diversion process, so that the implementation of diversion system can be done optimally. Thus, Indonesia as a just state of law can provide complete protection and justice for children from the conventional criminal justice systems Keywords: Child Criminal Court System, Diversion, Law Enforcement